Growth of critical thinking skills in middle school immersive science learning environments. (December 2022) - Alpizar, David; Vo, Thao; French, Brian F; Hand, Brian
Highlights: Modeling the growth of critical thinking skills is a challenge. Critical thinking trajectories of 5-8 th grades show change trajectory. Reading scores are related to initial status of critical thinking skills. Boys and girls appear to grow in these skills at comparable rates. Growth trajectories inform how these skills change in middle school. Abstract: Modeling the growth of critical thinking (CT) skills is a challenge that has not received much attention, especially among middle school students. There is insufficient evidence to support how CT skills change over time and how covariates may influence the trajectory of these skills among middle school students. This study addressed these issues by modeling CT skills across four years (5 th to 8 th grade) for middle school students with latent growth curve modeling. We examined whether the trajectory of CT skills is different for boys and girls and related to reading scores. Findings describe how CT growth increases among students during this developmental transition time. Results also show how reading scores relate to initial levels of CT skills in the 5 th grade and the growth across time. Implications for future research are discussed.